A MODERN ANALYSIS OF THE PROBLEMS OF “EPISTEMOLOGICAL OPTIMISM AND SKEPTICISM” - Kosbergenova, Nurzada Tolıbaevna (Educational Research in Universal Sciences, 2023)
In philosophy, the problem of doubt in the process of knowing the world and truth. An important method of skepticism in knowledge. Passive acceptance of the current regime of things, ruling opinions and other ethical-political terms. Philosophical skepticism is a school of philosophical thought.